The ETHICAL PRACTICES IN THE INDIAN PHARMACEUTICAL INDUSTRY: LESSONS LEARNED (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the setting of poor health indices in India, the question of ethical and economic efficiency in the supply and delivery of services becomes more complicated. First, this round table article provides an overview on ethical issues in health care, as well as the Indian health care sector and its facilities, the key actors in institutional roles in health care, and then a discussion of key ethical issues pertaining to the various players in health care: the physician and pharmaceutical industry. In the article's second section, a panel of experts from various geographical and organisational backgrounds discussed the challenges at hand.